Traditional and Emerging Integrated Marketing Communication Touchpoints Used in Effie Award-Winning Promotional Campaigns. Issue 2 (23rd February 2020) - Zwerin, Amanda; Clarke, Theresa B.; Clarke, Irvine
Abstract: This research presents a brief overview of Integrated Marketing Communications (IMC) research, including advertising effectiveness, and a discussion of the advertising competition landscape with a focus on the Effie Awards due to its incorporation of effectiveness as a key evaluation variable. Practitioners are increasingly being held accountable for outcomes of marketing efforts, thus it is important to understand factors that are associated with effective campaigns. We extend findings from previous studies by investigating IMC touchpoint data within award-winning Effie campaigns from 2011 to 2018. Data was analyzed from 609 winning campaigns to explore how touchpoints have evolved. On average, the mean number of touchpoints used in award-winning campaigns is increasing. Results further indicate several new categories of touchpoints used in recent campaigns, referred to as "Emerging" Touchpoint Categories as a comparison against prior findings, hereafter referred to as "Traditional" Touchpoint Categories.